2023
DOI: 10.1111/cge.14405
|View full text |Cite
|
Sign up to set email alerts
|

GPI‐anchoring disorders and the heart: Is cardiomyopathy an overlooked feature?

Allan Bayat,
Tobias Lindau,
Angel Aledo‐Serrano
et al.

Abstract: Glycosylphosphatidylinositol anchoring disorders (GPI‐ADs) are a subgroup of congenital disorders of glycosylation. GPI biosynthesis requires proteins encoded by over 30 genes of which 24 genes are linked to neurodevelopmental disorders. Patients, especially those with PIGA‐encephalopathy, have a high risk of premature mortality which sometimes is attributed to cardiomyopathy. We aimed to explore the occurrence of cardiomyopathy among patients with GPI‐ADs and to raise awareness about this potentially lethal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“… 74 Similarly, though a recent review suggested that IGD-related cardiomyopathy is under-reported, no individuals in our cohort had cardiomyopathy, including individuals with complex, often PIGA -IGD-related, structural cardiac disease. 75 Importantly, the significantly lower prevalence of DD/ID in our cohort expands the milder phenotypic spectrum of the IGDs: not only providing further evidence that children with IGDs can develop into adolescence with normal cognition and mild motor impairment, but also identifying novel and previously reported recurrent variants predictive of this milder phenotype with better long-term outcomes. 76 …”
Section: Discussionsupporting
confidence: 53%
“… 74 Similarly, though a recent review suggested that IGD-related cardiomyopathy is under-reported, no individuals in our cohort had cardiomyopathy, including individuals with complex, often PIGA -IGD-related, structural cardiac disease. 75 Importantly, the significantly lower prevalence of DD/ID in our cohort expands the milder phenotypic spectrum of the IGDs: not only providing further evidence that children with IGDs can develop into adolescence with normal cognition and mild motor impairment, but also identifying novel and previously reported recurrent variants predictive of this milder phenotype with better long-term outcomes. 76 …”
Section: Discussionsupporting
confidence: 53%